Effect of Boswellic Acid Administration on Blood Biochemical Profile of Sprague Dawley Rats in Cyclophosphamide-Induced Cardiotoxicity Conditions - Miranti Fardesiana Putri; Ietje Wientarsih; Bayu Febram Prasetyo; Vetnizah Juniantito (Britain International for Academic Research (BIAR) Publisher, 2022)
Cyclophosphamide (CP) is a chemotherapeutic agent that belongs to the alkylating agent group that is widely used in the treatment of cancer. Cardiotoxicity is often a side effect of using CP in medical therapy. In this study, 24 Sprague Dawley rats were randomly divided into 4 groups. Group 1 (K1) was given injection with aqua pro injection intraperitoneally (IP) once a week for 21 days. Group 2 (K2) was given IP CP with a dose of 50 mg/kg BW, once a week for 21 days. Group 3 (K3) was given boswellic acid extract at a dose of 250 mg/kg BW orally, every day for 21 days. Group 4 (K4) was given boswellic acid nanoparticles at a dose of 250 mg/kg BW orally, every day for 21 days. During the treatment the body weight of the rats was weighed every day. At the end of the treatment, the rats were euthanized and blood samples were taken for blood biochemical evaluation, namely CPK, LDH, AST, and ALT. The results showed that the levels of CPK, LDH, AST, and ALT in K2 were significantly higher (p<0.05) than K1, K3 and K4. Statistically, the results of CPK, LDH, AST and ALT in K3 and K4 were not significantly different (p<0.05) compared to K1. The two groups (K3 and K4) were not significantly different (p<0.05) but on average the CPK, LDH, AST, and ALT results in K4 had lower scores than K3. This can indicate the protective effect of boswellic acid and boswellic acid nanoparticles on the heart against cyclophosphamide-induced cardiotoxicity.